Novel technique for endoscopic ultrasound-guided gallbladder drainage to skip the needle tract dilation step: Efficacy of a 6-mm antimigration metal stent with a thin, tapered delivery catheter - Keiichi Hatamaru; Masayuki Kitano; Masahiro Itonaga; Yasunobu Yamashita; Takashi Tamura; Yuki Kawaji; Junya Nuta (International Journal of Gastrointestinal Intervention)
Background : Endoscopic ultrasound-guided gallbladder drainage (EUS-GBD) has been recognized as an effective treatment for patients at high risk for surgery. An antimigration metal stent with tapered thin delivery system has recently been developed. The aims of this study were to evaluate the feasibility, safety, and longterm outcomes of EUS-GBD using the new metal stent. Methods : Between April 2017 and March 2020, 21 patients with acute cholecystitis unsuitable for cholecystectomy underwent EUS-GBD using the metal stent. The stent was 6 mm in diameter and 6 cm in length, with a large flare at both ends for antimigration, and mounted in a 7.5 Fr delivery catheter, which requires no dilation devices. We retrospectively evaluated clinical and technical success, adverse events, and stent patency. Results : The technical and clinical success rates of EUS-GBD using the metal stent were 95.2% and 100%, respectively. For 75% of the patients, metal stents could be placed without dilatation of the needle tract. These patients had significantly shorter procedure time (23.6 ± 9.8 min) than patients requiring needle tract dilatation (38.4 ± 17.1 min; P=0.036). The median follow-up periods were 336 days (interquartile range [IQR] 152-919 days) and 1,135 days (IQR 1,009-1,675 days) for all and alive patients, respectively. No adverse events or recurrence of cholecystitis due to stent occlusion that occurred in any patient at follow-up was observed. Conclusion : In conclusion, EUS-GBD using the newly designed metal stent showed excellent safety and longterm outcomes, and may be suitable as an alternative treatment in patients who are unsuitable for cholecystectomy.